THE CONTEMPORARY HEALTH MANAGEMENT OF COVID-19 PANDEMIC CRISIS: BRIDGING FROM THE PAST TO THE FUTURE - Alabed, Hanadi (Universitas Islam Negeri Alauddin Makassar, 2022)
Contemporary management is a current process and updating science by which the manager plans, organizes, leads, and achieves organizational ultimate goals to accomplish hierarchical objectives and outcomes. Contemporary management skills also include overseeing individuals achieve institutional goals and objectives, maintaining power, ensuring discipline, and making sure that the strategy aligns with the company’s vision, mission, and long-term goals. There are many management theories that could be adopted by the managers of organizations and healthcare institutions and can be used as a guideline for successful and effective management styles at their management level. System Management and contingency theory are examples of the theories of contemporary management. COVID-19, for instance, is one of the global emergencies that required all levels of healthcare sector managers to respond appropriately and promptly and to be dynamic in their management style. In the light of the Covid-19 pandemic, this essay will address the management strategy and the macro factors impacting contemporary management, the contemporary management skills and attributes, the management system and change management theory, and the management style and practice, with some management insights and reflections from readings and experiences, conclusions, and recommendations. Keywords: Contemporary management, COVID-19, Crisis management, Health management, Resources management.